Penerapan Metode Diskusi Kelompok untuk Meningkatkan Hasil Belajar dalam Menyelesaikan Soal Cerita Bilangan Bulat - Encep Andriana; Siti Rokmanah; Fadila Monica (STKIP Andi Matappa Pangkep, 2022)
This research instead to determine the use of group discussion methods to improve student study result in solving integer problems in class VI B in Block C Elementary School. This research method uses quantitative research. The type of quantitative research is pre-experiment using One Group Pretest-Posttest Design. The population in this study were students of class VI B at Block C Elementary School. This study used 28 samples consisting of 12 male students and 16 female students. The research instrument that will be used is multiple choice tar given before learning (pretest) and after learning (posttest). The results obtained in this study are by comparing the results of the pretest and posttest as well as descriptive statistics (test the effectiveness of the quasi experiment. Based on the results of research that has been carried out the group discussion method can improve student study and result in solving problems. Integer story questions. The average posttest score was 91.42 from the average pretest score of 58.21. And also the group discussion method can be said to be effective in improving student study results.